2015
DOI: 10.4238/2015.may.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol and etomidate pretreatment on glucocorticoid receptor expression following induction of sepsis in rats

Abstract: ABSTRACT. The aim of this study was to determine the effect of etomidate and propofol pretreatment on the expression of glucocorticoid receptor and the prognosis of sepsis. The sepsis rat was used as a model. During glucocorticoid treatment, etomidate and propofol were applied alone or together at different time points. Survival curves, glucocorticoid receptor expression in the rat adrenal cortex, and inflammation levels were determined. The outcome of sepsis in rats was evaluated based on the combined utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, studies assessing the effects of etomidate on the expression and release of HMGB1 related to pro-inflammatory cytokines and NF-ĸB pathways under septic conditions are limited in number. The results of this study are similar to those of previous studies that suggest protective effects of etomidate on inflammation [ 32 , 33 ]. Because increased HMGB1 concentration correlates with organ injury and poor prognosis in sepsis [ 6 , 24 ], HMGB1 could be a potential target for sepsis treatment [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, studies assessing the effects of etomidate on the expression and release of HMGB1 related to pro-inflammatory cytokines and NF-ĸB pathways under septic conditions are limited in number. The results of this study are similar to those of previous studies that suggest protective effects of etomidate on inflammation [ 32 , 33 ]. Because increased HMGB1 concentration correlates with organ injury and poor prognosis in sepsis [ 6 , 24 ], HMGB1 could be a potential target for sepsis treatment [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in vitro or in vivo studies using animals have been performed to reveal the effects of etomidate on inflammation or mortality [ 15 , 31 ]. The anti-inflammatory effects of etomidate have been suggested in several previous studies [ 15 , 31 , 32 ], but in vivo studies using CLP-induced septic rats have offered inconsistent results regarding mortality [ 31 , 33 , 34 ]. Zhang et al reported that etomidate inhibited the serum mRNA expression of TNF-α and IL-6 and NF-ĸB activation, but the mortality of etomidate-treated septic rats was increased due to lymphocyte apoptosis rather than adrenal suppression [ 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations